How to develop and manage your own community seed bank: Farmers’ handbook (Booklet 2 of 3) [Ma’di version]. - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon R.; Gupta, Arnab (2023)
Ma’di edition of: Vernooy, R.; Bessette, G.; Sthapit, B.; Gupta, A. (2018) How to develop and manage your own community seed bank: Farmers’ handbook. Technical issues: Booklet 2 of 3. This handbook is a companion to Vernooy, R., Sthapit, B. and Bessette, G. (2020). Community seed banks: concept and practice. Facilitator handbook (updated version). Bioversity International, Rome, Italy (https://hdl.handle.net/10568/81286). The three booklets making up this handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Booklet 1 of 3 can be found here https://hdl.handle.net/10568/130989 and booklet 3 of 3 here https://hdl.handle.net/10568/131126. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. Translation and adaptation to the local language is encouraged. If you would like to receive a hard copy of the booklets or give feedback or suggestions for improvement, please contact r.vernooy@cgiar.org.